Embryonic thermal conditioning and post-hatch heat challenge alter hypothalamic expression of genes related to appetite, thermoregulation, and stress modulation in broiler chicks - Vaughan, Reagan; Sulaiman, Usman; Flynn, Annalise; Biase, Fernando; Meiri, Noam; Liu, Dongmin; Siegel, Paul; Cline, Mark; Gilbert, Elizabeth (Frontiers in Physiology, 2025)
The objective of this study was to determine the effects of an acute heat challenge on day 4 post-hatch on the transcriptome of several brain nuclei associated with thermal regulation, stress, and appetite. These included the paraventricular nucleus (PVN) of the hypothalamus, the pre-optic anterior/hypothalamic area (POAH), and the nucleus of the hippocampal commissure (nCPa), in broilers that were subjected to either control incubation conditions or embryonic heat conditioning (EHC). Nuclei were collected at three timepoints relative to the start of heat challenge (0, 2, and 12 h). Total RNA was isolated, and RNA-sequencing was performed. Transcript abundance was quantified, differentially expressed genes (DEGs) were identified, and Gene Ontology analyses were performed. In the nCPa, 469 DEGs were identified across the three timepoints. There were 0 DEGs at hour 0, 2 at hour 2, and 467 at hour 12. Gene Ontology analysis of nCPa samples at hour 12 revealed enrichment in five biological processes, namely, mitochondrial electron transport, mitochondrial respiratory chain complex 1 assembly, synaptic vesicle lumen acidification, protein export from the nucleus, and aerobic respiration. Most of these genes were downregulated, suggesting reduced activity in these processes in EHC chicks. In the POAH, a total of 18 DEGs were identified, with 0, 18, and 0 at hour 0, 2, and 12, respectively. Fewer differences were observed in the PVN, with only four DEGs identified. All four were upregulated in the EHC group, with two involved in hypothalamic thermal responses: vasoactive intestinal peptide transporter 1 (VIPR1) and caprin family member 2 (CAPRIN2). In the nCPa, no differences were detected between hour 2 and hour 0; however, the comparison between hour 12 and hour 2 yielded 9 DEGs. All except one were downregulated at hour 12. The hour 12 vs. hour 0 comparison revealed 49 DEGs, of which 24 were downregulated at hour 12. The results revealed pathways associated with energy metabolism were altered in response to EHC, with most differences in the nCPa. Surprisingly, the fewest differences were observed in the PVN. The findings highlight potential target regions, such as the nCPa, and metabolic pathways that may help better understand how EHC affects stress responses and energy homeostasis later in life.